Fracture behavior of discontinuous fiber-reinforced composite inlay-retained fixed partial denture before and after fatigue aging - Lassila Lippo; Mangoush Enas; Vallittu Pekka; Garoushi Sufyan (Elsevier, 2022)
Purpose: To evaluate the fracture behavior of inlay-retained fixed partial dentures (IRFPDs) made of experimental short fiber-reinforced composite (SFRC) computer-aided design/computer-aided manufacturing (CAD/CAM) block before and after cyclic fatigue aging.
Methods: Five groups (n=20/group) of three-unit posterior IRFPDs were fabricated. The first and second groups were CAD/CAM fabricated from experimental SFRC blocks or lithium-disilicate (IPS e.max CAD, IVOCLAR) materials, the third group comprised a three-dimensional-printed composite (Temp PRINT, GC), and the fourth and fifth groups comprised conventional laboratory flowable composite (Gradia Plus, GC) and commercial flowable SFRC (everX Flow, GC), respectively. All IRFPDs were luted into a metal jig with adhesive dual-cure resin cement (RelyX Ultimate, 3M ESPE). Half the IRFPDs per group (n=10) were subjected to fatigue aging for 10,000 cycles. The remaining half were statically loaded until fracture without fatigue aging. The load was applied vertically between triangular ridges of the buccal and lingual cusps. The fracture mode was visually examined using optical and scanning electron microscopy (SEM). Data were statistically analyzed using a two-way analysis of variance (ANOVA) followed by Tukey's HSD test.
Results: ANOVA revealed that IRFPDs made of experimental SFRC CAD/CAM had the highest (p<0.05) load-bearing capacity before (2624±463 N) and after (2775±297 N) aging among all groups. Cyclic fatigue aging decreased the load-bearing capacity (p>0.05) of all tested prostheses, except for the experimental SFRC CAD/CAM and conventional laboratory composite IRFPDs (p>0.05). SEM images showed the ability of discontinuous short fibers in the experimental SFRC CAD/CAM composite to redirect and hinder crack propagation.
Conclusion: CAD/CAM-fabricated IRFPDs made of experimental SFRC blocks showed promising performance in clinical testing in terms of fracture behavior.